Pendidikan Kristiani Transfromatif bagi Remaja dalam menghadapi Era Digital di GMIM Jemaat Sion Lobu - Ratulangi, Andrea Elfata; Sihombing, Liston; Paat, Devrialdo Daniel (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this study is to examine, analyze, and describe the implementation of Transformative Christian Education for teenager in facing the digital era, as well as to identify the obstacles encountered and the efforts made to overcome them. This research employs a qualitative method with a descriptive approach and was conducted at GMIM Sion Lobu. Data were collected through observation, interviews, and document studies. The results of data analysis and interpretation indicate that the implementation of Transformative Christian Education for teenager is necessary to prepare them to face the challenges of the digital era, particularly the various negative influences that arise. Based on these findings, it is recommended that special ministers, teenager ministry committees, and parents optimize the implementation of Transformative Christian Education. Through these efforts, the lives of teenager at GMIM Sion Lobu Congregations can experience tangible achievements in the form of transformation, in line with the vision of GMIM teenager, "Teenager for Christ".